Methods in soil mineralogy - Jusop, Shamshuddin (Universiti Putra Malaysia Press, 2011)
This book comprises eight chapters where the first chapter gives an introductory explanation on soil mineralogy. The word ‘mineral’ is defined as it is commonly used and the limitations of the subject field are clearly demarcated for the benefits of researchers and students. The next five chapters are concerned with explanation on the state-of-the-art methodologies in soil mineralogy such as X-ray diffraction analysis, thermal analysis, electron microscopy, thinsection and the study of light and heavy minerals in the coarse fraction of soil. Chapter 7 outlines and/or explains how charges on mineral surface can be determined in the laboratory, while Chapter 8 is about the applicability of data from the total analysis of the mineral component of soils in mineralogical studies.